DOES INTERFERON (IFN)S EXIST IN CRUSTACEA? - Dewi Syahidah; Leigh Owens (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2011)
The wide exploration of interferon (IFN)s in vertebrates for medical purposes has attracted researchers to investigate the existence of a similar role of interferon in other organisms such as invertebrates, including insects, and crustacea. A review of the literature indicates that there is no evidence of interferon existing either in insects such as D. melanogaster and A. gambiae which have had their genomes fully sequenced or in crustacea. However, a nonspecific antiviral state in crustacean, such as P. monodon can be efficiently triggered by both dsRNA and siRNA. The evidence suggests that anonymous cytokines, similar to interferon and not identical to any vertebrate IFNs, related to antiviral protection, do exist in crustacea. However, how widely spread of interferon immune response inducer or interferon-like molecules in this group is an important issue that remains to be explored.